(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
This paper develops a complex model of a photovoltaic power plant with an installed capacity of 9.99 MW. The model is created in PSCAD-EMTDC, which allows adjustment of active and reactive power. Based on the power adjustment, the P-Q diagram is determined at the connection point. At the same time, the plant under study is integrated into the National Energy System, so the P-Q diagram will also be determined based on measurements. Finally, the proposed model will be validated using measurements, and the photovoltaic power plant’s compliance with the technical requirements for interconnection will be verified. It should be noted that the power plant studied falls into category C. The conclusions highlight that the complex model enables valid validation of the photovoltaic power plant against all compliance requirements for category C power plants, which is essential for the actual assessment of grid integration.